The Impact of Intellectual Capital on Return of Fixed Assets and Firms Total Assets Return Which Listed On the Tehran Stock Exchange - Nezhad, Ali Aliyani; Yamrali, Oktay; Aboujafari, Mohammad Reza (Asian Economic and Financial Review, 2014)
Nowadays, there are a lot of differences in value of commercial corporations. Existing capitals other than physical capitals in balance sheet is the most important reason that researchers of capital market have focused on it. In this paper, hypotheses were set by using of Pulic model and were presented in the form of regression. The study was carried out in a five-year period, between the years 2008 to 2012, and data have been collected from audited financial statements of Tehran Stock Exchange. Regarding the subject of this study and limitations of information just 41 firms were chosen. The results of this research show that intellectual capital has impact on return of a firm’s total asset (financial performance) meanwhile it doesn’t have any effect on fixed asset’s return. The findings of this research are important because it claims that firm’s value doesn’t consist of just tangible assets and according to science progress the role of intangible assets in increasing firm’s value becomes much more important than tangible assets.